Degradation studies of proton exchange membrane water electrolysis cells with low platinum group metals – Catalyst coating achieved by atomic layer deposition - Sánchez Batalla, Beatriz; Laube, Armin; Hofer, André; Struckmann, Thorsten; Bachmann, Julien; Weidlich, Claudia (International Journal of Hydrogen Energy, 2022)
Activity and durability of a polymer electrolyte membrane (PEM) water electrolysis single cell, assembled with porous transport electrodes (PTEs) with a low catalyst loading were investigated for 500 h. A current density of 160 mA/cm2 and a high mass activity of 1368 A/gIr were achieved while operating at 60 °C with 1 mol/L sulfuric acid. The degradation of the cell was characterized using different electrochemical and physicochemical methods before, during and after operation of the electrolysis cell and a mean degradation rate for the cell of 67 μV/h was determined at 15 mA/cm2. To the best of our knowledge this is the first time that long-term performance of a PEM water electrolysis cell assembled with PTEs coated by ALD is investigated.<br

Long-term performance of PEM water electrolysis cells with 3D printed electrodes and low catalyst loading - Sánchez Batalla, Beatriz; Laube, A.; Hofer, André; Zallmann, S.; Körner, Carolin; Struckmann, T.; Bachmann, Julien; Weidlich, C. (International Journal of Hydrogen Energy, 2024)
Proton Exchange Membrane Water Electrolyzers (PEMEL) are promising for the production of green hydrogen, but costs have to be reduced and lifetime has to be improved. In this study we investigate PEMEL with low catalyst loading achieved by Atomic Layer Deposition (ALD) and 3D printing of the electrodes. Degradation processes were characterized and allocated using different electrochemical and physicochemical methods. The cell setup was optimized using Distribution of Relaxation Times Analysis (DRT) of the Electrochemical Impedance Spectroscopy (EIS) measurements and the long-term performance of the optimized cell was investigated using different electrolytes (sulfuric acid and deionized water).
CRIS-Team Scopus Importer:2025-02-04
Keywords: 3D printing; Degradation; Distribution of relaxation times; Electrochemical impedance spectroscopy; Low catalyst loading; PEM water electrolysis cells

Practically applicable water oxidation electrodes from 3D-printed Ti6Al4V scaffolds with surface nanostructuration and iridium catalyst coating - Hofer, André; Wachter, Sebastian; Döhler, Dirk; Laube, Armin; Sánchez Batalla, Beatriz; Fu, Zongwen; Weidlich, Claudia; Struckmann, Thorsten; Körner, Carolin; Bachmann, Julien (Electrochimica Acta, 2022)
This study establishes the applicability of 3D printing (additive manufacturing) towards the generation of titanium alloy scaffolds for water oxidation electrodes. The scaffolds can be subsequently nanostructured by electrochemical anodization to enhance their surface area and coated with iridium as the electrocatalyst. We focus on the characterization of the functional electrodes in process-relevant conditions (1 M HSO, 60 C, stirring) in terms of their performance and stability in a holistic manner. Various preparative conditions yield various patterns of performance and stability, as quantified by overpotentials in steady-state electrolyses, maximum current densities in dynamic voltammetry, surface roughness rf, and by overpotential increase, iridium loss, and decrease after 100 h of operation, on the other hand. In other words, the system is highly flexible and can be adapted to specific constraints depending on the application chosen.<br
Keywords: ALD; Electrochemistry; Heterogeneous catalysis; Iridium; Water splitting

Tubular membrane electrode assembly for PEM electrolysis - Laube, Armin; Hofer, André; Sánchez Batalla, Beatriz; Ressel, S; Chica, A.; Fischer, Simon; Weidlich, Claudia; Bachmann, Julien; Struckmann, Thorsten (International Journal of Hydrogen Energy, 2022)
Polymer electrolyte membrane (PEM) water electrolysis is already widely used for hydrogen production but still needs further cost reductions. While tubular cell designs might reduce production costs by extrusion production of cell components and small sealing lengths, catalyst coating methods like atomic layer deposition (ALD) might reduce catalyst costs significantly. This study demonstrates the feasibility of a tubular PEM electrolyzer membrane electrode assembly (MEA) for the oxygen half cell with 5.0 mm diameter. An extruded perfluorosulfonic acid (PFSA) cation exchange membrane is combined with a porous transport electrode (PTE) consisting of a titanium felt with a low iridium catalyst loading obtained by ALD. The performance is experimentally characterized in a complete tubular cell setup by polarization curve and ohmic resistance measurements. Operation in sulphuric acid at a cell voltage of 1.7 V and a cell temperature of 60 °C results in an overall current density of 55 mA cm−1 and an iridium mass activity 680 A g−1 which is up to 3 times larger than literature values. The high frequency ohmic resistance of the cell turns out to be 0.96 Ω cm−2. Up to the knowledge of the authors, this is the first time, that a tubular PEM electrolysis cell is designed, assembled and characterized.<br
Keywords: Cylindric cell design; PEM water Electrolysis; ALD catalyst Coating; Porous transport electrodes

Tubular PEM electrolysis cells with a 3D-printed oxygen electrode and ALD catalyst coating - Laube, Armin; Sánchez Batalla, Beatriz; Weidlich, Claudia; Hofer, André; Bachmann, Julien; Zallmann, S.; Körner, Carolin; Fischer, S.; Chica, A.; Struckmann, Thorsten (International Journal of Hydrogen Energy, 2023)
Polymer electrolyte membrane electrolysis (PEMEL) is a technology with a major role in linking the hydrogen production to renewable energy resources with a volatile behaviour such as wind and solar. High amounts of precious metals and a labour intensive production also make it a cost intensive technology. A tubular cell design has the potential to reduce production costs by co-extrusion of cells which feature a reduced sealing length. For the inner half cell, additive manufacturing (AM) of titanium offers a high degree of freedom for the electrode design to reach a high electric conductivity and active surface area. In combination with atomic layer deposition (ALD) of iridium catalyst a porous transport electrode (PTE) can be fabricated. Using planar test cell results and model based PTE design, this study demonstrates the feasibility of a tubular PEMEL cell consisting of an additively manufactured, iridium coated anode PTE in the inner half cell, an extruded membrane and a platinum coated graphite felt cathode PTE in the outer half cell. The outer titanium current collector can be replaced by an extruded graphite polymer compound current collector to reduce the amount of titanium without performance losses. The cell is operated at 60 °C in 1 mol L−1 sulphuric acid and experimentally characterized by polarization curves and electrochemical impedance spectroscopy (EIS). At 2.0 V cell potential a current density of ≈450mAcm−2 was reached corresponding to an iridium mass specific current density >1500Ag−1 which is significant larger than literature values.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Additive manufacturing; Cylindrical cell design; PEM water electrolysis